2014
DOI: 10.1063/1.4875059
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of electron emission from the grain boundaries of chemical vapour deposition diamond films by tunneling atomic force microscopy

Abstract: The emission of electrons from diamond in vacuum occurs readily as a result of the negative electron affinity of the hydrogenated surface due to features with nanoscale dimensions, which can concentrate electric fields high enough to induce electron emission from them. Electrons can be emitted as a result of an applied electric field (field emission) with possible uses in displays or cold-cathode devices. Alternatively, electrons can be emitted simply by heating the diamond in vacuum to temperatures as low as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 21 publications
(16 reference statements)
3
20
0
1
Order By: Relevance
“…This work has provided direct evidence that electron field emission from diamond surfaces originate preferentially from the diamond grain boundaries in doped-UNCD surfaces and not from the diamond grains or other topographical features. This is consistent with the model for electron field emission based on lowering of the emission threshold due to a reduction of the electron affinity of the diamond surface surrounding graphitic structures on the surface [47] and corroborates the findings of other groups [29,30,49,50,51]. As long as the grain boundaries remain relatively conducting compared to the bulk grains, electrons can travel from the contact at the reverse side of the Si substrate into the base of the film, then up to the grain boundaries and be emitted from the surface.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This work has provided direct evidence that electron field emission from diamond surfaces originate preferentially from the diamond grain boundaries in doped-UNCD surfaces and not from the diamond grains or other topographical features. This is consistent with the model for electron field emission based on lowering of the emission threshold due to a reduction of the electron affinity of the diamond surface surrounding graphitic structures on the surface [47] and corroborates the findings of other groups [29,30,49,50,51]. As long as the grain boundaries remain relatively conducting compared to the bulk grains, electrons can travel from the contact at the reverse side of the Si substrate into the base of the film, then up to the grain boundaries and be emitted from the surface.…”
Section: Discussionsupporting
confidence: 92%
“…However, the data from only one sample with 400×400 nm scale, it is hard to point out whether the diamond grains or grain boundaries were the actual conducting/emitting sites. Recently Harniman et al, [29] and V. Chatterjee et al [30] showed that the grain boundaries are the prominent electron emission sites for polycrystalline diamond films by using PeakForce-controlled tunneling atomic force microscopy (PF-TUNA) in ambient conditions, where the topographic and tunneling current information were collected under PeakForce feedback. However, in ambient conditions, the surface deformation mediated by surface contaminations and surface conducting layers, drastically affect the tunneling current and hence for the real detection of the electron emission sites [29,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…
The letter introduces a diagram that rationalizes tunneling atomic force microscopy (TUNA) observations of electron emission from polycrystalline diamonds as described in recent publications [1,2]. The direct observations of electron emission from grain boundary sites by TUNA could indeed be evidence of electrons originating from grain boundaries under external electric fields.
…”
mentioning
confidence: 83%
“…Eletrodos formados por filmes de diamante dopado com boro (DDB) têm sido alvo das atenções de muitos pesquisadores ao longo dos anos (1)(2)(3)(4)(5)(6)(7) devido a vantagens que incluem alta resistência à corrosão; ampla faixa de potencial de trabalho para a maioria dos solventes e eletrólitos; alta inércia química e eletroquímica; baixa sensibilidade ao oxigênio dissolvido; correntes residuais ou de fundo pequenas e estáveis, o que resulta numa excelente razão sinal/ruído; atividade eletroquímica reprodutível e alta condutividade elétrica (8) . O diamante em seu estado natural é um dos melhores isolantes presentes na natureza, podendo, porém, ter sua condutividade sensivelmente melhorada pela adição de dopantes (B, N, O, S) na rede cristalina deste material.…”
Section: Introductionunclassified